2017
DOI: 10.1590/1678-4162-8939
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stocking density on growth performance and welfare of juvenile tilapia ( Oreochromis niloticus ) in cages

Abstract: Intensification of tilapia production can cause negative implications on performance and welfare of fishes. Thus, it is essential to determine a correct density for optimal production. This study aimed to evaluate performance and animal welfare of juvenile Nile tilapia with an initial weight average of 30g (± 2.70) reared using three different stocking densities in floating net-cages. Fish were fed three times a day with feed containing 32% crude protein during 74 days. The experimental design was completely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
(8 reference statements)
3
12
0
2
Order By: Relevance
“…The study agrees with the findings of Vargesson[90] on zebrafish, Oppedal, Vågseth[91] on Salmon salar, Alhassan, Abarike[92] and Costa, Roubach[93] on Oreochromis niloticus, who reported that stocking densities influenced the growth and performances of fish. The study revealed that diet and stocking density played a vital role in the specific growth performance of zebrafish.…”
supporting
confidence: 92%
“…The study agrees with the findings of Vargesson[90] on zebrafish, Oppedal, Vågseth[91] on Salmon salar, Alhassan, Abarike[92] and Costa, Roubach[93] on Oreochromis niloticus, who reported that stocking densities influenced the growth and performances of fish. The study revealed that diet and stocking density played a vital role in the specific growth performance of zebrafish.…”
supporting
confidence: 92%
“…(2008) [7] . Lower stocking density resulted in the highest survival rate when compared to higher densities (Costa et al 2017) [8] . While Narejo et al (2010) [26] reported that survival was found to be negatively influenced by stocking densities.…”
Section: ) Between T-i and T-ii Treatments And Also Between Tc And T-iii But T-i And T-iimentioning
confidence: 99%
“…In general, in all species of animal for production, including fish, a high stocking density is associated with a decrease in growth, weight gain, and feed conversion rate (Tong et al 2012, Ardiansyah & Fotedar 2016, Fu et al 2016, Costa et al 2017, Reafey et al 2018, Long et al 2019. However, in this study, A. gigas showed a different pattern, weight gain, feed conversion rate, absolute growth rate, specific growth rate, feed conversion rate, biomass gain, and relative growth rate did not change under the effect of increasing stocking density.…”
Section: Discussionmentioning
confidence: 99%
“…Stocking density is, after feeding and nutrition, the most influential factor on the performance of most aquaculture species (Andrade et al 2015, Millán-Cubillo et al 2016, Arifin et al 2017, Shajib et al 2017, Long et al 2019, Lorenzen & Camp 2019. It determines, first of all, the quality of the rearing environment, and second, influence the comfort of the animals in their feeding, movement, resting (MacIntyre et al 2008, Person-Le Ruyet et al 2008, Tsuzuki et al 2008, Pinho et al 2016, Costa et al 2017 and thus the importance of studying in aquaculture.…”
Section: Introductionmentioning
confidence: 99%